The Impact of Light Pollution on the Star Photography - Xiong, Yansen (International Journal of Natural Resources and Environmental Studies, 2025)
Light pollution, resulting from artificial outdoor lighting, significantly impedes the visibility of celestial objects, posing challenges for both astronomical research and astrophotography. This study investigates light pollution across 40 of China’s largest cities, focusing on its relationship with economic indicators, population density, and geographic factors. By combining city-level data on GDP, population, and altitude, we identify patterns in luminous flux that reveal optimal locations for stargazing and astrophotography. The analysis shows that cities with lower economic activity and higher altitudes generally experience reduced light pollution, with Urumqi and Guiyang emerging as the most favorable locations for astrophotography based on combined economic and geographic characteristics. Findings indicate that urban planning and policy measures can play a critical role in managing light pollution, thereby supporting clearer skies and promoting sustainable development. This research provides a framework for identifying low-pollution observation sites and contributes to broader efforts to preserve dark skies for future generations.